Step-by-step explanation:
the inverse function of f(x) gives us for a specified y-value the original x-value that was used in f(x) to get us that y- value.
we can find the inverse function by inverting and transforming the original function from
y = f(x)
into
x = ...
and then we simply rename x to y and y to x to make it a "normal" function.
in our case (if you described it correctly above) the function is named g(x), but the same principles apply.
y = g(x) = -(1/2)x + 3
now we want to transit this into an equation of the form
x = ...
so, we add e.g. (1/2)x to both sides and get
(1/2)x + y = 3
then let's subtract y from both sides
(1/2)x = 3 - y
and then we multiply both sides by 2
x = 6 - 2y or -2y + 6
as last step we rename x to y and y to x
y = g-1(x) = 6 - 2x or -2x + 6
so, A) is correct